Nikolas Van Dam, The Struggle for Power in Syria. Sectarism, Regionalism and Tribalism in Politica, 1961-1978. London, Croom Helm Ltd. Publishers, 1979, pp. 147. - -, - (Estudios de Asia y África, 1981)
-